Human health risk assessment of pesticide residues in vegetable and fruit samples in Gujarat State, India. Issue 10 (October 2022) - P, Sivaperumal; Thasale, Rupal; Kumar, Dhirendra; Mehta, Tejal G.; Limbachiya, Riddhi
Abstract: The present study was initiated with the purpose to evaluate possible health risks associated with pesticide residues through consumption of vegetables and fruits by general population of Gujarat, India. A total of 1075 samples comprising of twelve different varieties of commonly consumed food commodities were collected from twenty-five divergent locations in Gujarat. The collected samples were extracted using QuEChERS method and analyzed for the presence of organophosphorus (OPs), organochlorine (OCs) and synthetic pyrethroids (SPs) pesticides using UHPLC-HR/MS, GC-μECD and GC-MS/SIM. The results indicated that 2.3% of vegetable and fruit samples showed the presence of pesticide residues exceeding maximum residue limits (MRLs). The results suggested that, detected residue levels in samples were within safe limits and their consumption will not pose any significant health risk to human. The outcomes present significant information regarding the status of vegetable and fruit contamination and pointed out the prerequisite for further studies with reference to monitoring of pesticides and other toxic contaminants in different samples for assessing cumulative health risk. Abstract : Pesticide residues, Fruits and vegetables, Dietary intake, Human consumption, Health risk.